ANALISIS GREEN TOURISM DI THAILAND: MENUJU PARIWISATA BERKELANJUTAN DALAM PERSPEKTIF EKONOMI DAN SUMBER DAYA MANUSIA - Saifuddin; Sugangga, Rayyan; Iradah Rahman; Syarifah Mahdiyah (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2025)
Thailand leads Southeast Asia in terms of foreign tourist arrivals. However, the rapid growth of the tourism industry often has adverse consequences for the environment. Contemporary tourism management has to deal with major issues such as pollution, habitat degradation, and overcapacity of tourist destinations. Therefore, the term “green tourism”, also known as “green tourism”, has emerged as an alternative to achieve a balance between environmental preservation and tourism industry development. The purpose of this article is to identify the concept and implementation of green tourism in Thailand as an effort towards sustainable tourism by reviewing its impact from an economic and human resources (HR) perspective. The article is written using a qualitative descriptive method approach with a literature study to describe in detail and in depth a certain phenomenon based on data and information obtained from various literature sources. The discussion of this article found that the role of education in encouraging pro-environmental behavior is also an important concern. Studies in Thailand show that additional years of formal education increase the likelihood of individuals to take knowledge-based environmentally friendly actions, such as the use of energy-saving tools, as well as appearing that majority religious principles or values have an impact on the implementation of Green Tourism in Thailand